Exploring the behaviour of dapped wet wall-to-wall connections under uniformly distributed load - Amril Hadri Jamaludin,; Noorsuhada Md Nor,; Muhhamad Nur Aizuddin Amri,; Amir Khomeiny Ruslan,; Ahmad Syauqi Md Hassan,; Soffian Noor Mat Saliah,; Muhammad Afiq Tambichik,; Mohd Azrizal Fauzi,; Shahrum Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The connection between two wall panels is the weakest part of the wall system and becomes the crucial point of failure. This paper presents the behaviour of two proposed types of wall-to-wall connections subjected to uniformly distributed load until failure, dapped wet and lightly vertically reinforced dapped wet connections. A total of twelve wall panels were prepared and constructed as six wall-to-wall connections, with three connections for each type. The acoustic emission (AE), maximum load (Pmax), strain and deflection characteristics were analysed and discussed to determine the behaviour of each wall-to-wall connection. The occurrence of cracks on the walls during the tests was also observed. The results showed that the Pmax for the wet and lightly vertically reinforced wall-to-wall connections of dapped concrete were 164.37 kN and 138.44 kN, respectively. From the distribution of AE, the highest energy was determined for the lightly vertically reinforced wall-to-wall connection, at 18000 eu. From the AE activity mapped on the crack pattern, it was observed that most AE activities occurred at the top of the wall, which corresponded strongly with the occurrence of cracks at the wall connection surface. Vertical cracks occurred in the connection areas, propagating from the top to the bottom. The major benefit of this study is the proposal for a new type of vertical wall-to-wall connection that can be used in prefabricated wall panel systems in industrialised building systems.